Dapagliflozin effects on exercise, cardiac remodeling, biomarkers, and renal and pulmonary function in heart failure patients: not as good as expected? - Mapelli, Massimo; Mattavelli, Irene; Salvioni, Elisabetta; Capra, Nicolò; Mantegazza, Valentina; Garlaschè, Anna; Campodonico, Jeness; Rubbo, Filippo Maria; Paganin, Chiara; Capovilla, Teresa Maria; Nepitella, Alessandro Alberto; Caputo, Rebecca; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSodium-glucose cotransporter-2 inhibitors (SGLT2-i) are standard therapy for heart failure (HF). We performed a holistic evaluation of dapagliflozin, including its effects on exercise performance, left ventricle (LV) reverse remodeling, cardiac biomarkers, fluid retention, and renal and pulmonary function.MethodsWe enrolled HF reduced ejection fraction (LVEF) outpatients (EF <40%) eligible for SGLT2-i and performed cardiopulmonary exercise tests (CPET), pulmonary function tests, bioelectrical impedance vector analysis, and laboratory and echocardiographic assessments at baseline (T = 0), after 2–4 weeks (T1), and after 6 months of treatment (T2).ResultsNone of the patients interrupted SGLT2-i for adverse events albeit follow-up was completed by 67 of 75 enrolled patients. At T2, mean LVEF increased (from 34.6 ± 7.8 to 37.5 ± 9.2%; p < 0.001) while end-diastolic (EDV) and end-systolic (ESV) volumes decreased [EDV: 186 (145–232) vs. 177 (129–225) mL, ESV: 113 (87–163) vs. 110 (76–145) mL; p < 0.001]. Peak oxygen intake was unchanged [peakVO2: 16.2 (13.4–18.7) vs. 16.0 (13.3–18.9) mL/kg/min; p = 0.297], while exercise ventilatory efficiency (VE/VCO2 slope) improved [from 34.2 (31.1–39.2) to 33.7 (30.2–37.6); p = 0.006]. Mean hemoglobin increased (from 13.8 ± 1.5 to 14.6 ± 1.7 g/dL; p < 0.001), while renal function did not change after a transient worsening at T1. NT-proBNP, ST-2, and hs-TNI did not change as overall body fluids and quality of life assessed by KCCQ. NYHA class improved (p=0.002), paralleled by a decrease of MECKI (Metabolic Exercise test data combined with Cardiac and Kidney Indexes) score, from 3.3% (1.9–8.0) to 2.8% (1.2–5.7), suggestive of a positive impact on 2 years prognosis (p < 0.001).ConclusionsDapagliflozin induced positive LV remodeling, improvement of exercise ventilatory efficiency, and NYHA class but without peakVO2 fluid status and cardiac biomarkers changes.